Ancient Indian Wisdom and the OECD Guidelines: A Cross-Civilizational Dialogue on Responsible Business Conduct - Vijayasimha, Narendra (Intellectual Journal of Academic Research, 2025)
This paper explores the deep consonance between the OECD Guidelines for Multinational Enterprises and the ethical frameworks embedded within ancient Indian texts. It examines each of the eight core principles of the OECD - ranging from transparency and human rights to environmental stewardship and anti-corruption. The paper traces their philosophical and practical counterparts in scriptures such as the Vedas, Upanishads, Ramayana, Mahabharata, Artha Shastra, Manu Smriti, and Bhagavad Gita. Through detailed textual analysis, the study demonstrates how Sanathana Dharma offers a timeless and nuanced vision of corporate responsibility, inclusion, justice, and sustainability. Key concepts such as Sama Darshana (equal vision), Vidya-Dhana (knowledge as a gift), and Dharmic Governance align closely with contemporary global norms around ethical business practices. The paper not only bridges ancient and modern paradigms of governance but also proposes a spiritually enriched, culturally inclusive foundation for ethical enterprise in the 21st century.